1994
DOI: 10.2331/fishsci.60.519
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia of Coho Salmon <i>Oncorhynchus kisutch</i> Infected with Erythrocytic Inclusion Body Syndrome (EIBS) Virus

Abstract: Anemia caused by hemolysis occurred in coho salmon Oncorhynchus kisutch infected with the erythrocytic inclusion body syndrome (EIBS) virus. Bilirubin levels were significantly higher in the plasma of diseased fish than in healthy fish. Hyperbilirubinemia occurred in fish infected with EIBS virus. Erythrocytic superoxide dismutase activities were induced in the diseased fish. The liver bilirubin level of diseased fish was much higher than that of control fish, while the total bile acid level in the plasma of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Recently, HSMI-like disease in the presence of PRV has been reported in Chilean coho salmon [19], which showed lesions in yellow livers, pale gills, splenomegaly, jaundice, hemopericardium, epicarditis, and myocarditis [19]. These pathological changes seem to be consistent with the lesions of EIBS-affected coho salmon in Japan [1, 8, 9]. Based on genomic segment S1 sequences, the Chilean PRV isolates from coho salmon were more genetically diverse (subgenotypes Ia and Ib) than those from Atlantic salmon, and some formed a distinct new phylogenetic cluster, designated genotype II [19].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, HSMI-like disease in the presence of PRV has been reported in Chilean coho salmon [19], which showed lesions in yellow livers, pale gills, splenomegaly, jaundice, hemopericardium, epicarditis, and myocarditis [19]. These pathological changes seem to be consistent with the lesions of EIBS-affected coho salmon in Japan [1, 8, 9]. Based on genomic segment S1 sequences, the Chilean PRV isolates from coho salmon were more genetically diverse (subgenotypes Ia and Ib) than those from Atlantic salmon, and some formed a distinct new phylogenetic cluster, designated genotype II [19].…”
Section: Introductionmentioning
confidence: 71%
“…A histopathological examination of EIBS-affected coho salmon also showed necrosis of the muscle fibers in the cardiac ventricle and atrium [8]. Hyperbilirubinemia and the accumulation of bilirubin in the liver [9] may be one of the causes of the jaundice and yellow-colored livers of diseased coho salmon. The causative agent of EIBS is an icosahedral virus, approximately 70–80 nm in diameter, and the virions are often observed within membrane-bound structures that are frequently associated with the cellular membranes [7, 10].…”
Section: Introductionmentioning
confidence: 99%
“…This tropism of PRV in Atlantic Salmon erythrocytes and its ability to form inclusions is of interest in the context of the Jaundice Syndrome described herein, because there have been reports describing viral inclusions in salmonid erythrocytes (collectively termed EIBS) that have been associated with jaundice (Sakai et al . ). In these previous reports on EIBS, electron microscopy, acridine orange staining and chloroform sensitivity measurements demonstrated the virus(es) causative of EIBS were likely enveloped particles (Leek ; Arakawa et al .…”
Section: Discussionmentioning
confidence: 97%
“…Among salmonid species, jaundice occurs in Atlantic Salmon, Chinook Salmon, coho salmon, Oncorhynchus kisutch (Walbaum), and Rainbow Trout O. mykiss (Walbaum), with cause attributed to either erythromycin toxicity (Haukenes & Moffitt 2002), exposure to industrial effluents (Everall, Nitchell & Robson 1992) or potentially due to a viral infection (Sakai et al 1994). There has also been the sporadic occurrence of a jaundice condition in seawater-cultured coho salmon in Chile, where the cause of these outbreaks remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…SOD is a cytosolic enzyme unique for scavenging superoxide radicals. Supplementation with dietary vitamin E or carotenoids has significant effects on liver antioxidant enzyme activities in sea bream (Sparus aurata L.) (Mourente et al, 2002), salmon (Sakai et al, 1994), characin (Wang et al, 2006) and juvenile tiger prawn (Penaeus monodon) fed diets with carotenoids have lower SOD activities than those of fish fed a control diet. Yang et al (2010) reported that dietary carotenoids result in lower muscle SOD activity in white shrimp (Litopenaeus vannamei) than that in shrimp fed the control diet.…”
Section: Discussionmentioning
confidence: 99%